2013
DOI: 10.1016/j.jrp.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

On the similarity between exchangeable profiles: A psychometric model, analytic strategy, and empirical illustration

Abstract: Analyses of profile similarity are widespread in personality psychology, but their apparent simplicity masks difficult psychometric and statistical issues. We present a psychometric framework that addresses an important challenge (i.e., profile normativeness) in examinations of dyadic exchangeable profiles. In addition, we present an analytic strategy accounting for non-independence that often arises in analyses of profile similarity, facilitating integrated examinations of variables at dyadic and individual l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…There is an emerging recognition that examining all coefficients in the same analysis can reveal interesting effects (Bleidorn et al, 2012; Borkenau & Zaltauskas, 2009; Furr et al, 2007, 2007; Furr & Funder, 2004; Furr & Wood, 2013; Leary & Allen, 2011; Locke, Zheng, & Smith, 2014). For instance, Biesanz and Human (2010) found that experimentally manipulating motivation among judges to attain accurate perceptions of targets was not associated with increased judgment agreement as indexed by an overall profile correlation.…”
Section: Discussionmentioning
confidence: 99%
“…There is an emerging recognition that examining all coefficients in the same analysis can reveal interesting effects (Bleidorn et al, 2012; Borkenau & Zaltauskas, 2009; Furr et al, 2007, 2007; Furr & Funder, 2004; Furr & Wood, 2013; Leary & Allen, 2011; Locke, Zheng, & Smith, 2014). For instance, Biesanz and Human (2010) found that experimentally manipulating motivation among judges to attain accurate perceptions of targets was not associated with increased judgment agreement as indexed by an overall profile correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses were conducted via AMOS 19. Model 6 in Table 3 of the online supplemental document accompanying Furr and Wood (2013) provides AMOS syntax that was subsequently adapted for the current analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Similarity indices are applied in ecology, for example, to assess similarity between ecological communities in terms of their species composition (e.g., Hastings et al 2012), in genetics to characterize similarity between gene profiles (e.g., Deshpande et al 2013), and in psychology to measure similarity between personality profiles (e.g., Furr and Wood 2013). In some cases, the presence or absence of common features is of interest, while in others, the degree of commonality is important and can be assessed by various measures of distance.…”
Section: Similarity Index Methodsmentioning
confidence: 99%